PENGARUH FASHION INFLUENCER, PROMOSI DIGITAL, DAN PERSEPSI GAYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK STREETWEAR OLEH GENERASI Z - Vina Dwi Yanti; Haryanto Tanuwijaya; Sri Suhandiah (MANAJEMEN DEWANTARA, 2026)
This study purposes to analyze the influence of fashion influencers, digital promotion, and style perception on streetwear purchase decisions among Generation Z. The research employed a quantitative approach using a survey method. A five-point Likert scale was used in an online survey to gather data from 103 Generation Z respondents in Surabaya who actively use social media and have purchased streetwear products within the last six months. Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software was used to analyse the data.The findings indicate that fashion influencers, digital promotion, and style perception have a positive and significant effect on purchase decisions. Digital promotion shows the strongest influence, followed by fashion influencers and style perception. The coefficient of determination (R²) value of 0.712 indicates that 71.2% of the variance in purchase decisions is explained by the three independent variables, while the predictive relevance (Q²) value of 0.478 demonstrates that the model has good predictive capability. These findings indicate that streetwear purchase decisions among Generation Z are influenced by the integration of digital promotion strategies, influencer credibility, and consumers’ style perception aligned with their self-identity.